Identifying Patients for Overdose Prevention With ICD-9 Classification in the Emergency Department, Massachusetts, 2013-2014. (September 2016) - Ellison, Jacqueline; Walley, Alexander Y.; Feldman, James A.; Bernstein, Edward; Mitchell, Patricia M.; Koppelman, Elisa A.; Drainoni, Mari-Lynn
The national rise in opioid overdose deaths signifies a need to integrate overdose prevention within healthcare delivery settings. The emergency department (ED) is an opportune location for such interventions. To effectively integrate prevention services, the target population must be clearly defined. We used ICD-9 discharge codes to establish and apply overdose risk categories to ED patients seen from January 1, 2013 to December 31, 2014 at an urban safety-net hospital in Massachusetts with the goal of informing ED-based naloxone rescue kit distribution programs. Of 96, 419 patients, 4, 468 (4.6%) were at increased risk of opioid overdose, defined by prior opioid overdose, misuse, or polysubstance misuse. A small proportion of those at risk were prescribed opioids on a separate occasion. Use of risk categories defined by ICD-9 codes identified a notable proportion of ED patients at risk for overdose, and provides a systematic means to prioritize and direct clinical overdose prevention efforts.